Impact of Online Marketing on Teenagers in India - Tripathi, Veena (International Journal of Social Sciences and Management, 2016)
Online Marketing is quickly evolving in front of our eyes and it is almost impossible to reject and hide from this new form of media. “This shift in consumer influence indicates a need and an opportunity for companies to reprioritize the mix of communication channels they use to reach their consumers”. The study discusses the attitude of teens towards brand selection due to Online Marketing comprising apparel market in India. This research is divided in three parts to understand The Impact of Online Marketing on Brand Selection by Teenagers. 1) Strategy behind Online Marketing to Teenagers. 2) Power of Online Marketing on Teens in Brand Selection. 3) Benefits and worries of Online Marketing on Teens. Int. J. Soc. Sc. Manage. Vol. 3, Issue-4: 277-280